2017
DOI: 10.1186/s40425-017-0213-x
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab induced myxedema crisis

Abstract: BackgroundNivolumab is an anti-programmed cell death (anti-PD-1) monoclonal antibody that is approved by Food and Drug Administration for treatment of metastatic non-small cell lung cancer, metastatic melanoma, relapsed Hodgkin lymphoma and advanced renal cell cancer. We report a rare case of myxedema crisis induced by nivolumab in a patient with metastatic squamous cell carcinoma of lung.Case presentationFifty three-year old woman with metastatic squamous cell carcinoma currently on treatment with nivolumab p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 11 publications
0
29
0
1
Order By: Relevance
“…63 Of the patients with thyrotoxicosis, 80% later developed hypothyroidism. Thyroid storm 64 and myxedema crisis 65 have rarely been reported in patients treated with ICI. The median onset of thyroid dysfunction occurs 4 weeks after starting therapy.…”
Section: Thyroid Toxicitymentioning
confidence: 99%
“…63 Of the patients with thyrotoxicosis, 80% later developed hypothyroidism. Thyroid storm 64 and myxedema crisis 65 have rarely been reported in patients treated with ICI. The median onset of thyroid dysfunction occurs 4 weeks after starting therapy.…”
Section: Thyroid Toxicitymentioning
confidence: 99%
“…Hypothyroidism, in most cases, remains permanent, requiring long-term levothyroxine replacement ( 6 , 33 ). Although the majority of the cases had been classified as grade 1 or 2 irAEs, serious complications of hypothyroidism, for example, myxedema crisis ( 72 ) or myopathy ( 73 ) have been rarely reported. Hypothyroidism-associated myopathy was characterized by severe myalgias, arthralgias, and significant creatine kinase elevation, which could be reversed by levothyroxine replacement therapy.…”
Section: Immune Checkpoint Inhibitor-induced Thyroid Disordersmentioning
confidence: 99%
“…These findings are in agreement with other retrospective case series, which found that the majority of endocrine irAEs occur during the first 15 weeks of therapy. 16,23 Although the majority of cases of thyroid abnormalities are low grade, 9 and only rarely require withholding ICI treatment or initiating immunosuppressive therapy, a few cases of thyroid storm 24 or severe hypothyroidism 25,26 after the use of ICIs have been reported. It is important to note that presentation with more severe endocrinopathies may become more frequent in patients treated outside of a clinical trial setting, because older patients and those with cardiac dysfunction, who commonly are underrepresented in clinical trials, 27,28 are at high risk of thyroid disorderrelated cardiovascular events.…”
Section: Clinical Presentationmentioning
confidence: 99%